MICROPHOTOGRAPHIC ATLAS OF NORMAL HISTOLOGY (1925) — PIONEERING CONTRIBUTION OF ALEXANDER Đ. KOSTIĆ TO MEDICAL EDUCATION - Puškaš, Nela (HEALTH CARE, 2025)
During its early years, the Faculty of Medicine faced numerous challenges, one of which was the lack of medical literature, especially in the Serbian language, which was particularly pronounced. In histology, an additional challenge was the presentation and identification of microscopic specimens during practical classes because it relied solely on drawings. An innovation in teaching was introduced in 1925 with the Microphotographic Atlas of Normal Histology, authored by Aleksandar Kostić. It was the first histological atlas intended for students of the Medical Faculty in Belgrade and one of the first in the world to contain complete microphotographs. Kostić prepared the set of microphotographs for the atlas in the Photography Department, established at the Institute in 1924. By publishing this atlas, Aleksandar Kostić established his scientific-photographic mission, making him a pioneer in medical photography both in Serbia and in the then Kingdom of Serbs, Croats, and Slovenes.
Keywords: Aleksandar Đ. Kostić, microphotography, histology atlas